Differential mode voltage reduction in dual inverters used to drive open-end winding interior permanent magnet synchronous motors - Lee, Hyung Woo; Lee, Deog Ho; Lee, Kyo Beum (Journal of Power Electronics, 2023)
In this paper, a level-shift-based voltage modulation method for dual inverters used to drive open-end winding interior permanent magnet synchronous motors is presented. Notably, the conventional level-shift-based voltage modulation method used for dual inverters presents a disadvantage, since the differential mode voltage (DMV) significantly increases compared with that in the basic control method of dual inverters. This defect can be attributed to the fact that the conventional level-shift-based voltage modulation method uses a voltage vector combination that generates the maximum DMV peak value. To address this problem, the proposed method reduces the DMV by explicitly switching the voltage vectors that generate a large DMV. In this paper, the DMV generation process in a dual-inverter system is analyzed. Moreover, the DMV tendencies of the conventional and proposed methods are divided into operating regions according to the modulation index, which are further analyzed. The effectiveness and performance of the proposed voltage modulation method for a dual inverter are verified based on simulation and experimental results.
Keywords: Differential-mode voltage; Dual inverters; Interior permanent magnet synchronous motor; Level shift; Level-shift modulation; Modulation methods; Open-end winding interior permanent magnet synchronoi motor; Open-end windings; Shift modulation; Voltage modulations; Differential mode voltage; Dual inverter; Level-shift modulation; Open-end winding interior permanent magnet synchronous motor